Hyperosmolar non-ketotic diabetic coma and rhabdomyolysis. Issue 819 (January 1994) - Trump, D.; O'Hanlon, S.; Rinsler, M.; Sharp, P.
Abstract : Rhabdomyolysis is a rare but potentially fatal complication of hyperosmolar states. We report a case of severe hyperosmolar non-ketotic diabetic coma causing rhabdomyolysis in a young man. Despite very high levels of creatine kinase there was no detectable myoglobinuria. Creatine kinase estimation should be a standard investigation in all patients presenting with a hyperosmolar state.